Assembly-style making: How structured making serves as an on-ramp to creativity and engineering design - Lukowski, Sarah; Goeke, Megan; Schmit, Bette; Bequette, Marjorie (Frontiers in Psychology, 2023)
Makerspaces, workspaces where families can explore materials and tools collaboratively, can provide an opportunity for creative expression and early engineering learning in community spaces. The present study examined a cardboard-focused museum makerspace that included an assembly-style activity. Assembly-style making uses instructions to support makers. Such activities have been critiqued as limiting creativity and engineering thinking. However, makers who are less comfortable in makerspaces may benefit from assembly-style activities helping to scaffold their entry into the space. We explored these criticisms and potential benefits of assembly-style making through developing case studies of video data taken by families in a makerspace. Visitors made creative and personally meaningful creations when engaged in assembly style making. Moreover, assembly-style making mediated a family less comfortable with making to get started in the space alongside ample evidence of families following engineering design processes. Contrary to popular belief, assembly-style making offers an important support to novice makers, without eliminating creativity and engineering design processes, and should be considered in the mix of activities available in makerspaces to support makers of all levels of comfort in making.